Pengembangan Sistem Pelayanan Pasien berbasis Web (Studi Kasus: Puskesmas Rejowinangun Kabupaten Trenggalek) - Threecia Agil Regitasari; Adam Hendra Brata; Randy Cahya Wihandika (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
Rejowinangun public health center is one of the medical services in Trenggalek which serves 7 villages. There are counters for running the services, which are registration, treatment, payment, and pharmacy. In operation, Rejowinangun public health center has several challenges. One of them is duplicate in patient call list data between two or more patients that can cause confusion among patients and delay serving time. That can happen because patient calls are done by sound amplifiers by patient name and village data. If the patient data is not the same as the medical record, the patient has to wait again. Based on the mentioned problems, a Web-Based Patient Service System has been developed with some features such as patient registration, data search, patient calls, data processing related to medical records, and service data reporting. It is expected to solve the problem. System developed with the waterfall model. This research found 8 actors with 78 functional requirements and 1 non-functional requirement. This system was tested using unit testing and validation testing. Unit testing done by white-box testing with PHP Unit found a 100% valid result. Validation testing is divided into two, functional and non-functional. Functional validation testing was done by using black-box testing and got a 100% valid result. Non-functional validation testing is done by using compatibility testing with the Sortsite application and the result is that the system can run well on all browsers.